Sodium- and Phosphorus-Based Food Additives: Persistent but Surmountable Hurdles in the Management of Nutrition in Chronic Kidney Disease - Gutiérrez, Orlando M. (Advances in chronic kidney disease, 2013)
Sodium- and phosphorus-based food additives are among the most commonly consumed nutrients in the world. This is because both have diverse applications in processed food manufacturing, leading to their widespread use by the food industry. Since most foods are naturally low in salt, sodium additives almost completely account for the excessive consumption of sodium throughout the world. Similarly, phosphorus additives represent a major and “hidden” phosphorus load in modern diets. These factors pose a major barrier to successfully lowering sodium or phosphorus intake in patients with CKD. As such, any serious effort to reduce sodium or phosphorus consumption will require reductions in the use of these additives by the food industry. The current regulatory environment governing the use of food additives does not favor this goal, however, in large part because these additives have historically been classified as generally safe for public consumption. To overcome these barriers, coordinated efforts will be needed to demonstrate that high intake of these additives is not safe for public consumption and as such should be subject to greater regulatory scrutiny.